(untitled) (Journal of Comparative & International Higher Education, 2022)
This qualitative research in-progress investigates the bilingual ideology and identity of EMI (English-medium-instruction) teachers and students at a Chinese medical university that aims to enrich the understanding of bi/multilingualism in the EFL (English as a Foreign Language) context from domestic stakeholders’ perspectives. The researcher conducted a series of semi-structured interviews with Chinese medical content teachers and students throughout an academic term. Supplementary research materials include written materials, such as lecturers’ PowerPoint slides and institutional documents. The preliminary findings suggest that the teachers and students present diverse ideological stances towards bilingualism, and they perform an ambivalent identity: privileged, yet incompetent to fulfil the expected bilingual identity by self and others, due to ideological and practical constraints. The potential discussion and implications are given in the summary.